OPTIMAL DESIGN OF SUSPENSION SYSTEM BASED ON IMPROVED PARTICLE SWARM-TABOO SEARCH ALGORITHM - WANG Jun; TIAN ZhongXu (Jixie qiangdu)
Aiming at the problem that the vibration isolation effect of the engine mount system of an off-road vehicle is not ideal under idling condition,a dynamic model of the engine mounting system is established with the crankshaft center line and the rear end face of the first cylinder as the origin. In order to solve the natural frequency and mode shape of the suspension system,the method of combining the jorisk decomposition with the Jacobian method is used. At the same time,the suspension system is proposed by the improved particle swarm optimization tabu search optimization algorithm with the decoupling rate of the main direction of the system excitation force as the optimization goal. After optimization,the decoupling rate of the main direction of the suspension system is improved. Finally,ADAMS is used to verify and analyze the natural frequency and energy distribution of the optimized mounting system,which further verifies the feasibility of the optimization method.